SIBLING RELATIONSHIP IN SIR ARTHUR CONAN DOYLE’S STORIES: “THE ADVENTURE OF THE GREEK INTERPRETER” AND "THE ADVENTURE OF THE BRUCE-PARTINGTON PLANS" - ., Ismiati (Conscientia - Journal on Language, Literature, and Culture, 2024)
This paper presents the sibling relationship between Sherlock Holmes and Microft Holmes as seen in Sir Arthur Conan Doyle’s two stories “The Adventure of the Greek Interpreter” and “The Adventure of the Bruce-Partington Plans.” The objectives of this research were to find out the sibling relationship among these two adults Mr. Sherlock Holmes and Mr. Microft Holmes. The methods applied in the research are the library research method for collecting the data and the descriptive qualitative method in analyzing the data. The theoretical approach is the psychological approach. The finding is that the sibling relationship between Sherlock and Microft takes form in a positive way, a warm sibling relationship. The older Microft supports the younger Sherlock. They help each other in solving the cases.